Preparation and characterization of CoeRu/TiO2/MWCNTs electrocatalysts in PEM hydrogen electrolyzer - Perica Paunovic, Dafinka Stoevska Gogovska, Orce Popovski, Antonia Stoyanova, Evelina Slavcheva, Elefteria Lefterova, Peter Iliev, Aleksandar T. Dimitrov, Svetomir Hadzi Jordanov (Elsevier, 2011)
The subject of this study is preparation and characterization of hypoehyper d-electrocatalysts with reduced amount of precious metals aimed for water electrolysis. The studied electrocatalysts contain 10% mixed metallic phase (Co:Ru ¼ 1:1 wt., Co:Ru ¼ 4:1 wt. and Co:Ru:Pt ¼ 4:0.5:0.5 wt.), 18% TiO2 as a crystalline anatase deposited on multiwalled carbon nanotubes (MWCNTs). Previously, MWCNTs were activated in 28% nitric acid. As a reference electrocatalyst for hydrogen evolution reaction, corresponding electrocatalysts with pure Pt metallic phase and mixed CoPt (Co:Pt ¼ 1:1 wt.) metallic phase were prepared. Also, as a reference electrocatalyst for oxygen evolution reaction, electrocatalyst with pure Ru metallic phase was prepared. The prepared electrocatalysts were structurally characterized by means of XPS, XRD, TEM, SEM and FTIR analysis. Electrochemical characterization was performed by means of cyclic voltammetry and potentiodynamic method in the PEM hydrogen electrolyzer. The range of the catalytic activity for hydrogen evolution of studied electrocatalysts was the following: CoRuPt (4:0.5:0.5) > CoPt (1:1) > Pt > CoRu (1:1) > CoRu (4:1). The order of the catalytic activity for oxygen evolution was the following: CoRu (1:1) > Ru > CoRu (4:1) > Pt > CoRuPt (4:0.5:0.5) > CoPt (1:1).